Characteristics of heart rate variability in women with polycystic ovary syndrome: A retrospective cross-sectional study. Issue 38 (September 2018) - Ji, Hae Ri; Woo, Hye Lin; Park, Young Jae; Hwang, Deok Sang; Lee, Jin Moo; Lee, Chang Hoon; Jang, Jun Bock; Park, Kyoung Sun
Abstract : Abstract: We aimed to compare the modulation of the autonomic nervous system (ANS) in women with polycystic ovary syndrome (PCOS) with that in healthy ovulatory women on the basis of heart rate variability (HRV), and to analyze the characteristics of the ANS in PCOS. In a retrospective chart review, HRV, body mass index, and physical examination data in women with PCOS and those with regular menstrual cycles were collected. Approval from the institutional review board (IRB) was obtained (IRB No. 2017-05-007-001) for this study. The mean outcomes were the values of HRV in the time [standard deviation of all normal R-R intervals (SDNN), the square root of the sum of the squares of the differences between the adjacent normal R-R intervals (rMSSD), and the mean heart rate turbulence (mean HRT)] and frequency [total power (TP), very-low-frequency power (VLF), low-frequency power (LF), normalized low-frequency power (LF norm), high-frequency power (HF), normalized high-frequency power (HF norm), and LF/HF ratio] domains. Differences between the 2 groups were analyzed by Mann-Whitney U test, using SPSS for Windows (version 22.0). There was no significant difference in the values of the time domain (SDNN, rMSSD, and mean HRT) between the groups. In the frequency domain, women with PCOS showed significantly higher LF (598.63 ± 94.38 vs 459.13 ± 163.64, P  = .028), LF norm (48.64 ± 3.39 vs 36.49 ± 2.82, P  = .009), and LF/HF ratio (1.49 ± 0.31 vs 0.73 ± 0.13, P  = .009) than the control group. HF norm was significantly lower in the women with PCOS than in the controls (51.38 ± 3.39 vs 63.51 ± 2.82, P  = .009). The TP, VLF, and HF showed no significant difference between the groups. The results of the present study indicated that PCOS is related to increased sympathetic modulation in HRV.